Community Service Provider's Stories: COVID-19 Impacts and Vulnerable Canadians - Nimo Bokore; Jillian Premachuk (Journal of Sociological Research, 2024)
In 2020 a global health pandemic began causing significant life challenges for most populations around the world. For vulnerable groups in Canada, like newcomers and refugees, the COVID19 global health crisis amplified pre-existing inequalities and barriers. Given the previous understandings of racial inequality in Canada, we began an online discussion with a group of social service providers to explore how newcomers and refugees are impacted by the social lockdowns, physical distance, and the closures of many services. As a result, we collected informative stories that tell how the pandemic disproportionately and distinctly impact newcomers and refugees, resulting in new challenges finding employment, access to educational services for their families, and maintaining an adequate social and spiritual connection. We also found out how community service provision drastically changed throughout the COVID-19 pandemic, resulting in additional challenges and barriers for marginalized communities.